Bilateral paranasal sinus fungal balls: A retrospective cohort study in 28 patients over a 21-year period. Issue 33 (19th August 2022) - Kim, Jong Seung; Kwon, Sam Hyun; Kim, Jung Soo; Heo, Sung Jae
Abstract : Paranasal fungal balls are rare entities for which a recent increase in reported cases has been observed. Fungal balls are most commonly unilateral, and there are few bilateral cases in the literature. Here we report the clinical features of bilateral fungal balls in 24 patients treated in our institution over the past 20 years. In this retrospective study, we reviewed the medical records of 5279 patients who underwent endoscopic sinus surgery performed by a single surgeon from January 1996 to December 2016 at a tertiary care center in order to identify patients diagnosed with fungal balls confirmed histopathologically. Demographic data and radiologic findings of patients with bilateral fungal balls were compared with those who had unilateral fungal balls. Multiple logistic regression test was used to compare demographic information between patients with unilateral and bilateral fungal balls. The most commonly involved sinus in bilateral cases was maxillary (87.5%), followed by ethmoid (37.5%) and sphenoid (33.3%). Of the 24 patients, 19 were female, and patient age ranged from 45 to 83 years, with an average of 65.1 years. Common existing comorbidities were hypertension (45.8%), diabetes (29.2%), cardiac problem (16.7%), cerebral infarction (8.3%), pulmonary tuberculosis (8.3%), and lung cancer (4.2%). The clinically relevant features of patients diagnosed with bilateral fungal balls from our review include advanced age and immunocompromised status compared to those with unilateral fungal balls. These features contribute to the clinical distinction of bilateral fungal ball disease from unilateral fungal balls and invasive fungal sinusitis.